Do government environmental audits reduce air pollution? Evidence obtained from Lanzhou - Chen, Tianyou; Li, Ji (Frontiers in Public Health, 2024)
Introduction This study investigates the effectiveness of government environmental audits in mitigating air pollution. Specifically, it focuses on a pilot project conducted in Lanzhou City by the former Ministry of Environmental Protection. The research employs a regression discontinuity design to empirically assess the impact of these audits on air quality. Methods The study utilizes a regression discontinuity design to evaluate the impact of the government environmental audits. The primary outcome variable is the Air Quality Index (AQI). The analysis includes extensive robustness checks, such as sensitivity testing for optimal bandwidths of key pollutants, adjusting for precipitation levels, and conducting various robustness tests to ensure the reliability of the results. Results The findings reveal a significant decline in the AQI following the implementation of the environmental audits. The AQI decreased from 31 to 25 during and after the audit period. Additionally, the study observed a notable increase in precipitation levels, suggesting potential environmental improvements. Robustness tests further confirm the reliability of the regression results. Discussion The research outcomes demonstrate the effectiveness of government environmental audits in reducing air pollution. By supervising local governments in the implementation of environmental protection policies, these audits contribute to improved air quality. The findings highlight the importance of targeted interventions and policy enforcement in addressing environmental challenges.